SISTEM INFORMASI PENGGAJIAN PADA PT.TONGKANG MAS CABANG PENINJAUAN - Destiarini Destiarini; Abdul Rahman; Afriantamtomi Afriantamtomi (INTECH, 2023)
Today in the implementation of an employee payroll system in several companies, it is still possible for errors or corruption to occur when many use program packages such as Microsoft Word and Microsoft Excel, for example at PT. The Tongkang Mas Review Branch still uses a payroll information system manually, making it possible for the delivery of results from a data processing to be slow and less effective. So that on the part of the company experienced material losses and on the part of employees the service needs have not been served properly and adequately. Based on these findings and research, the authors try to analyze and design an employee payroll information system at PT. Tongkang Mas the Review Branch. So that it is hoped that later it can reduce the occurrence of misuse of information and be able to serve the information needs of employees quickly and accurately. The method used in conducting this research uses system analysis work steps. In analyzing and designing a system by Tavri D. Mahyuzir which consists of problem definition, feasibility study, system design, system detail, implementation, maintenance, and system evaluation. From the development of this system, the author uses the Microsoft Access application to produce an employee payroll information system design consisting of general system design, input design, output design, and process design, as well as program display design which can later increase work efficiency and effectiveness and increase usage. computer resources.